ORGANIZATION OF STAKEHOLDER ENGAGEMENT AS A FACTOR IN INCREASING THE EFFICIENCY OF CORPORATE GOVERNANCE - V. Makovkina; I. Semeykina (Вестник университета)
The article discusses the issues of corporate interaction organization between stakeholders, which solution directly affects on the quality of corporate governance. Considering the problems of the organization of interaction with stakeholders, the experience of Russian companies to identify the stakeholders and their ranking, as well as the methods of interaction organization with them, the authors conclude that the most important issue related to the assessment of the cooperation effectiveness nowadays has no methodological support.